How Is Power Shared in Africa?. Issue 2 (March 2015) - Francois, Patrick; Rainer, Ilia; Trebbi, Francesco
<x xml:space="preserve">Abstract</x> Is African politics characterized by concentrated power in the hands of a narrow group (ethnically determined) that then fluctuates from one extreme to another via frequent coups? Employing data on the ethnicity of cabinet ministers since independence, we show that African ruling coalitions are surprisingly large and that political power is allocated proportionally to population shares across ethnic groups. This holds true even restricting the analysis to the subsample of the most powerful ministerial posts. We argue that the likelihood of revolutions from outsiders and coup threats from insiders are major forces explaining allocations within these regimes. Alternative allocation mechanisms are explored. Counterfactual experiments that shed light on the role of Western policies in affecting African national coalitions and leadership group premia are performed.